Scrotal Lipoblastoma with Radiological and Histological Correlation - Rousslang, Lee K.; Burr, Cole R.; Wood, Jonathan R. (Indian Journal of Radiology and Imaging, 2021)
Lipoblastomas are rare benign mesenchymal tumors comprised primarily mature adipocytes, which are most commonly found in infants and children younger than 3 years. They are usually found in the extremities, trunk, head, neck, and retroperitoneum, although cases occurring in the scrotum have been reported. Due to its rarity, there is a relative paucity of literature describing its imaging and management. We present a rare case of a scrotal lipoblastoma, and discuss the current imaging strategies to differentiate this adipocytic tumor from other more common paratesticular masses, including aggressive neoplasms such as rhabdomyosarcomas. Knowledge of the radiological appearance of lipoblastoma can provide the correct diagnosis and prevent unnecessary orchiectomy.
Keywords: adipocytic tumor; lipoblastoma; mesenchymal tumors; paratesticular mass; rhabdomyosarcoma